Carbon quantum dots (CQDs) based composites photocatalyst for wastewater purification - Fakhira Faaiqah, Hasan; Nur Aisha Wahida, Mohd Zahidi; Vivi Safitri, Bahar; Umi Rabiatul Ramzilah, P. Remli; Azrina, Abd Aziz (Trans Tech Publications, 2022)
A comparative study of the Carbon Quantum Dots (CQDs) based composites photocatalyst for water purification was carried out. New finding of CQDs and TiO2 have demonstrated significant advantage since it provides environmentally friendly for photocatalytic degradation of methyl orange (MO) dye. CQDS and TiO2 were prepared by using hydrothermal method. The CQDs and CQDS/TiO2 were fully characterized by using transmission electron microscope (TEM) to identify the size range and shape that involve in the adsorption process. The synthesized CQDs and CQDs/TiO2 had small semi spherical morphology with 5 nm in size. The result of photocatalytic activity revealed that there is photocatalytic degradation of MO in the presence of only pure CQDs and CQDs/TiO2 composites which the value of concentration decreased against time. CQDs/TiO2 exhibited higher photocatalytic activity, which indicated that both CQDs and TiO2 played important roles for the high photocatalytic activity under visible light irradiation.